HOW TO SOLVE HUME'S PROBLEM OF INDUCTION. (13th September 2017) - Jackson, Alexander
ABSTRACT: This paper explains what's wrong with a Hume-inspired argument for skepticism about induction. Hume's argument takes as a premise that inductive reasoning presupposes that the future will resemble the past. I explain why that claim is not plausible. The most plausible premise in the vicinity is that inductive reasoning from E to H presupposes that if E then H. I formulate and then refute a skeptical argument based on that premise. Central to my response is a psychological explanation for how people judge that if E then H without realizing that they thereby settled the matter rationally.